تصور الطلاب عن كفاءة مدرسي اللغة العربية التعليمية بالمدرسة الثانوية الإسلامية الحكومية الأولى مالانج - Maulidya, Hanifah; Hasanah, Mamluatul (Maharaat Lughawiyyat: Jurnal Pendidikan Bahasa Arab, 2024)
مستخلص البحث التصور هو رؤية الشخص لشيء ما، من حيث الرؤية والاستجابة والفهم. الهدف من هذا البحث هو لمعرفة تصورات الطلاب للكفاءة التعليمية لمعلمي اللغة العربية في المدرسة الثانوية الإسلامية الحكومية الأولى مالانج. هذا البحث هو بحث كمي وصفي تم إجراؤه في المدرسة الثانوية الإسلامية الحكومية الأولى مالانج. كانت العينة المستخدمة في هذه الدراسة جميعًا طلاب الفصل الحادي عشر للعلوم الطبيعية 2 في المدرسة الثانوية الإسلامية الحكومية الأولى مالانج، بإجمالي 34 شخصًا. استخدمت هذه الدراسة تقنيات جمع البيانات في شكل استبيان ومعالجتها عن طريق جدولة البيانات المقدمة بجداول التكرار والنسب المئوية. وكانت نتائج هذه الدراسة: استبيان حول كفاءة المعلم التعليمية أفاد بعبارات إيجابية بنسبة 80٪ وبيانات سلبية بنسبة 20٪. ذكرت هذه النسبة أن الكفاءة التعليمية لمعلمي اللغة العربية كانت جيدة لأن النسبة كانت في الفاصل الزمني بين 61-80. نتائج هذه الدراسة تجيب على فرضية قبول Ha ورفض Ho. ABSTRACT Perception is a person's view of something, both in terms of vision, response, and understanding. The purpose of this study is to determine students' perceptions of the pedagogical competences of Arabic teachers at MAN 1 Malang. This research is a research with a descriptive quantitative approach conducted at MAN 1 Malang. The sample used in this study were all students of class XI IPA 2 at MAN 1 Malang, totaling 34 people. This study used data collection techniques in the form of questionnaires and processed by means of tabulating data presented with frequency and percentage tables. The results of this study is a questionnaire about teacher pedagogic competence stated positive statements by 80% and negative statements by 20%. This percentage stated that the pedagogic competence of Arabic teachers at MAN 1 Malang stated well because the percentage was in the class interval between 61-80. The results of this study answer the hypothesis that Ha is accepted and Ho is rejected.